THE USE OF EU LLL PROJECTS TO ENHANCE LANGUAGE INSTRUCTION IN NON-FORMAL EDUCATION IN LATVIA - Karklina, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The present papers deals with the use of support mechanism for language instruction in the context of lifelong learning, which is of utmost importance for individual growth and for society as a whole. Although adults prefer the traditional learning /teaching environment, new worldwide processes in language instruction have brought terms such as plurilingualism, intercultural competence, language skill development, and communicative competence into everyday life. Through the creation of open space for intercultural dialogue, the communicative skills of adult learners are promoted, and a sustainable environment for continuous language learning is created. The author has analyzed the development and integration of authentic intercultural space with the practical teaching of adults, as well as their introduction and use in the learning/teaching environment in order to enhance the language acquisition process.